The Effect of High-Performance Human Resources Practices on Innovative Work Behavior Through Work Engagement and Psychological Capital - Purwaningrum, Indria Sari; Yulianti, Praptini (Manunggal Halim Jaya, 2026)
In this context, the purpose of the study is to examine the influence of HPHRP on Innovative Work Behavior (IWB) at Office X Surabaya, as well as to investigate the role of work engagement and psychological capital as mediators. The method used in this study is a quantitative approach with a causal design. Data were collected through an online questionnaire distributed to 121 respondents using a purposive sampling technique. The independent variable in this study is High Performance Human Resource Practices, while the dependent variable is Innovative Work Behavior. Work Engagement and Psychological Capital function as mediating variables that are expected to explain the relationship between High Performance Human Resource Practices and Innovative Work Behavior. Using a quantitative explanatory methodology, the research employed Structural Equation Modeling with Partial Least Squares (SEM-PLS), which was implemented in this work using SmartPLS software. A structured survey was used to gather information from 121 employees in Office X. The findings reveal a positive relationship between high-performance human resource practices and innovative work behavior, considering the mediating roles of Work Engagement and Psychological Capital.